Dietary fibre intake is associated with reduced risk of lung cancer: a Japan public health centre-based prospective study (JPHC). (30th March 2022) - Cai, Honglin; Sobue, Tomotaka; Kitamura, Tetsuhisa; Ishihara, Junko; Murai, Utako; Sawada, Norie; Iwasaki, Motoki; Yamaji, Taiki; Inoue, Manami; Tsugane, Shoichiro
Abstract: Background: Several epidemiological studies have been conducted to draw consistent conclusions regarding the effect of dietary fibre on lung diseases and lung cancer. However, the effect of dietary fibre on the incidence of lung cancer remains unclear in an Asian population. Methods: We investigated the association between the intake of total dietary fibre and dietary fibre from different food sources and lung cancer incidence in a Japan public health centre-based prospective study (JPHC). A total of 73 405 participants (33 012 men and 40 393 women) aged 45–74 years were eligible for our study. Cox proportional hazards models were used to calculate hazard ratios (HRs) and 95% confidence intervals (CIs). Results: During a median follow-up of 18.0 years, 1546 (1042 men and 504 women) newly diagnosed cases of lung cancer were ascertained. In the multivariable models, total dietary fibre intake was inversely associated with lung cancer risk in men, the HRs Q5 vs Q1 (95% CI) were 0.77 (0.62 to 0.94), P -trend = 0.020. Dietary fibre intake from vegetables was protectively associated with lung cancer risk in men [HR Q5 vs Q1 (95% CI): 0.80 (0.64 to 0.99), P- trend = 0.053]. However, no such association was observed in women. Conclusions: In men, a high intake of total dietary fibre may have preventive benefits for lung cancer incidence: dietary fibre intake from vegetables was associated with a lower incidence of lung cancer. However, similar associations did not appear in women. Further investigations are required to confirm the association between dietary fibre and lung cancer risk in women.